1997
DOI: 10.1097/00008390-199706001-00381
|View full text |Cite
|
Sign up to set email alerts
|

Epitrochlear lymph nodes as a site of melanoma metastasis

Abstract: Background:The incidence of epitrochlear lymph node metastasis for patients with melanomas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…A possible exception to consider is when clinically palpable disease presents in the unusual basin. Hunt et al described 10 patients who had therapeutic epitrocheal lymphadenectomy for clinically evident disease [63]. Six patients underwent simultaneous axillary lymphadenectomy and three of these had occult metastatic melanoma.…”
Section: Unusual Sites Of Metastasesmentioning
confidence: 99%
“…A possible exception to consider is when clinically palpable disease presents in the unusual basin. Hunt et al described 10 patients who had therapeutic epitrocheal lymphadenectomy for clinically evident disease [63]. Six patients underwent simultaneous axillary lymphadenectomy and three of these had occult metastatic melanoma.…”
Section: Unusual Sites Of Metastasesmentioning
confidence: 99%
“…b ''In series'' nodes receive afferent lymphatics from a cutaneous primary and send efferent lymphatics to a sentinel node in the major basin; if the major basin sentinel node is negative, no regional lymphadenectomy would be indicated even if the in transit sentinel node contains tumor. c ''In parallel'' nodes receive afferent lymphatics from a cutaneous primary but send efferent lymphatics to a nonsentinel node in the major basin; if a major basin sentinel node is negative, there would still be a substantial risk of metastatic disease within that major basin and lymphadenectomy would be appropriate to consider frequent in interval and minor basin nodes than major basin nodes, 1,8,9 but the reported rates of tumor involvement are clearly high enough to justify excising and analyzing in transit nodes whenever feasible. Based on available data, a positive interval or minor basin node seems to have essentially the same impact on prognosis as a positive major basin node.…”
mentioning
confidence: 99%
“…2,3 Hunt et al reported that epitrochlear node metastasis occurred in only 1.1% of upper limb primary melanomas. 4 However, Smith et al reported that the incidence of metastasis in epitrochlear nodes is 18% if primary melanoma is located on the forearm or hand lesions, especially on the ulnar distribution or within 3-5 cm of the elbow. 5 In our patient, primary melanoma was located on the forearm (around the elbow), and epitrochlear node metastasis occurred 2 years after her operation when she was pregnant.…”
Section: Discussionmentioning
confidence: 99%